Strategies for Self-Mastery and Physical Education Learning During the COVID-19 Pandemic - Eko Purnomo; Firunika Intan Cahyani; Nina Jermaina; Donie Donie; Eddy Marheni; Martio Mairifendi; Rizki Fitri Rahima Uulaa (IJORER : International Journal of Recent Educational Research, 2022)
Self-control strategy is a way for a person to determine how to control himself. The purpose of this study was to examine how much influence online learning has on students' self-control in physical education subjects. Researchers used a Likert scale questionnaire as the medium to get data from respondents . The results showed that the self-mastery strategy for online learning resulted in students who tended to be passive but had good self-control. Then, we found that the self-control strategy needed by students is the enthusiasm and motivation of physical education teachers. So that students are not bored during the process of making assignments. Then the results of this study indicate that when online learning takes place, students tend to be passive and bored.However, we also found that students had good self-control even though the results of their assignments did not meet the learning modules, such as being respectful to the teacher and to their groupmates.